QED corrections to polarized deep-inelastic and semi-inclusive deep-inelastic scattering - Gakh, G.I.; Merenkov, N.P.; Shekhovtsova, O.N. (Вопросы атомной науки и техники, 2001)
Leading-log model-independent QED corrections in DIS of unpolarized electron off tensor-polarized deuteron are considered. Same approach was used for investigation of semi-inclusive DIS of electron by nucleus with detection of hadron and scattered electron. Calculations are based on covariant parametrization of polarization and use of Drell-Yan like representation to describe radiation by initial and scattered electron. Applications to polarization transfer from polarized electron to detected hadron and to scattering by polarized target are considered. DIS of unpolarized electron on tensor-polarized deuteron with tagged collinear photon radiated from initial-state electron are investigated.